Intermittent Hypoxia Exposure Can Prevent Reductions in Hemoglobin Concentration After Intense Exercise Training in Rats - Weng, Xiquan; Chen, Hao; Yu, Qun; Xu, Guoqing; Meng, Yan; Yan, Xu; McConell, Glenn; Lin, Wentao (Frontiers in Physiology, 2021)
Intense exercise training can induce low concentrations of hemoglobin, which may be followed by maladaptation. Therefore, it is important for athletes to prevent low concentrations of hemoglobin during intense exercise training. In this study, we explored whether different protocols of intermittent hypoxic exposure (IHE, normobaric hypoxia, 14.5% O2) could prevent the exercise training-induced reduction in hemoglobin concentration in rats. Six-week-old male Sprague-Dawley rats were subjected to progressive intense treadmill exercise training over three weeks followed by three weeks of training with IHE after exercise. IHE lasted either 1 h, 2 h, or 1 h + 1 h (separated by a 3-h interval) after the exercise sessions. Hematological parameters, including hemoglobin concentration [(Hb)], red blood cells (RBCs), and hematocrit (Hct), and both renal and serum erythropoietin (EPO) were examined. We found that intense exercise training significantly reduced [Hb], RBCs, Hct, food intake and body weight (P < 0.01). Analysis of reticulocyte hemoglobin content (CHr) and reticulocyte counts in the serum of the rats suggested that this reduction was not due to iron deficiency or other cofounding factors. The addition of IHE after the intense exercise training sessions significantly alleviated the reduction in [Hb], RBCs, and Hct (P < 0.05) without an obvious impact on either food intake or body weight (P > 0.05). Increase in reticulocyte count in the rats from the IHE groups (P < 0.05 or P < 0.01) suggests that IHE promotes erythropoiesis to increase the hemoglobin concentration. Furthermore, the addition of IHE after the intense exercise training sessions also significantly increased the concentration of renal EPO (P < 0.05), although the increase of the serum EPO level was statistically insignificant (P > 0.05). The different IHE protocols were similarly effective at increasing renal EPO and preventing the training-induced decreases in [Hb], RBCs, and Hct. Collectively, this study suggests that IHE may be used as a new strategy to prevent intense exercise training-induced reductions in [Hb], and deserves future exploration in athletes.